Extracellular protein secretion optimization in Escherichia Coli by signal peptide mutation and additive supplementation [electronic resource] - Mohd. Anuar Jonet, 1985- (2012)
Thesis (Doktor Falsafah (Kejuruteraan Bioproses)) - Universiti Teknologi Malaysia, 2012